The correlation between reading and mathematics ability at age twelve has a substantial genetic component - Davis, O; Band, G; Pirinen, M; Haworth, C; Meaburn, E; Kovas, Y; Harlaar, N; Docherty, S; Hanscombe, K; Trzaskowski, M; Curtis, C; Strange, A; et al. (Springer Nature, 2014)
Dissecting how genetic and environmental influences impact on learning is helpful for maximizing numeracy and literacy. Here we show, using twin and genome-wide analysis, that there is a substantial genetic component to children's ability in reading and mathematics, and estimate that around one half of the observed correlation in these traits is due to shared genetic effects (so-called Generalist Genes). Thus, our results highlight the potential role of the learning environment in contributing to differences in a child's cognitive abilities at age twelve.